Association of Pregnancy Intentions With Substance Use During Early Pregnancy. Issue 1 (January 2022) - Young-Wolff, Kelly C.; Slama, Natalie; Sarovar, Varada; Conway, Amy; Tucker, Lue-Yen; Goler, Nancy; Terplan, Mishka; Ansley, Deborah; Adams, Sara R.; Armstrong, Mary Anne
Abstract : Objectives: The goal of this study was to evaluate the association between pregnancy intentions and substance use in early pregnancy among pregnant women receiving prenatal care in a large, integrated healthcare system. Methods: The sample comprised 29, 787 Kaiser Permanente Northern California pregnant women (12.1% aged <25, 36.4% non-Hispanic White) screened for prenatal substance use in 2018 via a self-reported questionnaire and urine toxicology test given as part of standard prenatal care (at ∼8 weeks gestation). Multivariable logistic regression models tested for associations of pregnancy intentions with prenatal substance use (any use and specific substances) by self-report and/or a positive urine toxicology test. Results: Adjusting for covariates, women with an unintended pregnancy (23.9% of the sample) had higher odds of any prenatal substance use than women with an intended pregnancy (28.8% vs 16.1%; adjusted odds ratio [aOR] = 1.80, 95% confidence interval [CI]:1.67–1.93). Having an unintended pregnancy was also associated with higher odds of using alcohol (14.4% vs 10.4%; aOR = 1.73, 95%CI:1.59–1.89), cannabis (15.6% vs 5.6%; aOR = 1.91, 95%CI:1.73–2.11), nicotine (3.8% vs 1.3%; aOR = 2.33, 95%CI:1.92–2.82), pain medication (2.3% vs 1.2%; aOR = 1.64, 95%CI:1.32–2.03), and stimulants (0.8% vs 0.3%; aOR = 1.85, 95%CI:1.23–2.79) early in pregnancy. Discussion: Having an unintended pregnancy was associated with higher odds of substance use during early pregnancy. Connecting women of reproductive age with health education about pregnancy prevention and recognition of early signs of pregnancy, effective contraception, and early screening and interventions for prenatal substance use may help to reduce prenatal substance use and its associated consequences.